2022
DOI: 10.1136/bcr-2021-247937
|View full text |Cite
|
Sign up to set email alerts
|

Copper-histidine therapy in an infant with novel splice-site variant in theATP7Agene of Menkes disease: the first experience in South East Asia and literature review

Abstract: Menkes disease (MD) is an X linked recessive multi-systemic disorder of copper metabolism, resulting from an ATP7A gene mutation. We report a male infant aged 4 months who presented with kinky hair, hypopigmented skin, epilepsy and delayed development. Magnetic resonance imaging (MRI) of brain demonstrated multiple tortuosities of intracranial vessels and brain atrophy. Investigation had showed markedly decreased serum copper and ceruloplasmin. The novel c.2172+1G>T splice-site mutation in the ATP7A gene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(60 reference statements)
1
2
0
1
Order By: Relevance
“…On the other hand, the ATP7A gene is expressed more in horned cultivars than in hornless breeds, which further proves that ATP7A genes may affect the formation and even size of horns. We found that the ATP7A gene is specifically highly expressed in soft horns and skin tissues, but almost not expressed in other internal organs, combined with previous studies ( Panichsillaphakit et al, 2022 ), indicating that the ATP7A gene is closely related to the function of the skin, may play a role in the keratinization of the skin, and participate in the formation process of horn sheaths. In four animals, humans, cattle, pigs and sheep, the ATP7A gene is only highly expressed in the skin of horned animals, sheep.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the ATP7A gene is expressed more in horned cultivars than in hornless breeds, which further proves that ATP7A genes may affect the formation and even size of horns. We found that the ATP7A gene is specifically highly expressed in soft horns and skin tissues, but almost not expressed in other internal organs, combined with previous studies ( Panichsillaphakit et al, 2022 ), indicating that the ATP7A gene is closely related to the function of the skin, may play a role in the keratinization of the skin, and participate in the formation process of horn sheaths. In four animals, humans, cattle, pigs and sheep, the ATP7A gene is only highly expressed in the skin of horned animals, sheep.…”
Section: Discussionsupporting
confidence: 84%
“…Early detection is hindered by the lack of newborn screening and overlap with other disorders. Mutations in the ATP7A gene lead to copper deficiency, affecting the nervous system [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…The primary treatments for MD patients are copper injections or oral supplements, which, if begun early, may improve the patient's prognosis and quality of life. Nonetheless, the majority of MD patients pass away before turning three years old, and the prognosis is typically dismal [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Опублікований досвід на цю тему показує, що парентеральне введення міді в будь-якій формі відновлює циркулюючу мідь і церулоплазмін до референтних рівнів, на відміну від перорального прийому міді. Разом із тим, хоча низькі запаси міді в печінці швидко поповнюються за допомогою парентеральної терапії, вміст міді в мозку під час лікування збільшується лише поступово, якщо взагалі зростає [41].…”
Section: вступunclassified